Teaching Factory Learning Has Not Been Effective in Increasing the Entrepreneurial Spirit of Vocational High School Students - Agung Winarno; Eting Kumala Sari (Department of Management, Faculty of Economics, Universitas Negeri Malang, 2019)
The purpose of this study is to determine the role of teaching factory implementation in Vocational High Schools  in increasing  the entrepreneurial spirit of students.  This  research used a  descriptive qualitative research approach  that is  case studies;  data collection is done by observation, documentation, and in-depth interviews. The results of the study showed that the implementation was carried out  following  industry standards,  the evaluation was carried out during the process and performance of the final good/service. In general teaching,  factoring can improve student skills in production,  yet  the development of entrepreneurial spirit  relatively  has not improved much. The main inhibiting factor of this learning is related to the lack of understanding of  creating  student entrepreneurial spirit but  it  is more focused on improving the student skill on production.